Pengaruh Disiplin dan Pelatihan Kerja terhadap Kinerja Pegawai di UPPPD Wilayah Jakarta Barat - Dita Sari Edy Saputri; Furi Indriyani (Pusat Riset dan Inovasi Nasional, 2026)
Employee performance is an important factor in supporting the success of public services, especially in government agencies that deal directly with the public. Efforts to improve employee performance need to be supported by the implementation of good work discipline and the implementation of job training that is appropriate to employee needs. This study aims to analyze the effect of work discipline and job training on employee performance at the Regional Tax Collection Service Unit (UPPPD) of West Jakarta. This study uses a quantitative method, data collection techniques are carried out by distributing questionnaires to employees with a population of 78 respondents. Sampling uses a total sampling technique. Data analysis was carried out using SPSS version 26 through multiple linear regression tests, t-tests, F-tests, and coefficient of determination (R²) tests. The results of the study indicate that work discipline has a positive and significant effect on employee performance with a significance value of 0.000 <0.05 and a calculated t-value of 11.577. Job training also has a positive and significant effect on employee performance with a significance value of 0.000 <0.05 and a calculated t-value of 11.368. Simultaneously, work discipline and job training significantly influence employee performance, with a calculated F-value of 132.931 and a significance level of 0.000 < 0.05. The coefficient of determination indicates that these two variables explain 78.0% of the variation in employee performance (R² = 0.780), while the remaining 22.0% is influenced by other variables outside this study.